2006
DOI: 10.1534/genetics.105.055145
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Nucleo-cytoplasmic Cross-Talk Results in Donor Cell mtDNA Persistence in Cloned Embryos

Abstract: Mitochondrial DNA is an extranuclear genome normally maternally inherited through the oocyte. However, the use of nuclear transfer can result in both donor cell and recipient oocyte mitochondrial DNA persisting through to blastocyst and being transmitted to the offspring. The degree of donor mitochondrial DNA transmission appears to be random and currently no evidence exists to explain this phenomenon. To determine whether this is a dilution factor or directly related to the transcriptional status of the donor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Induction of nuclear factors involved in the biogenesis of mitochondria has been described in response to mtDNA depletion [46]. Accordingly, mtDNA content in undifferentiated iPSCs appeared significantly decreased in comparison to somatic cells (Fig.…”
Section: Low Mitochondrial Content and Mtdna Copy Number In Ipscs Andmentioning
confidence: 75%
“…Induction of nuclear factors involved in the biogenesis of mitochondria has been described in response to mtDNA depletion [46]. Accordingly, mtDNA content in undifferentiated iPSCs appeared significantly decreased in comparison to somatic cells (Fig.…”
Section: Low Mitochondrial Content and Mtdna Copy Number In Ipscs Andmentioning
confidence: 75%
“…However, the reduction in mtDNA copy number that takes place during preimplantation development in larger mammals, due to there being no expression of the key mtDNA replication factors (Lloyd et al 2006;Bowles et al 2007;Spikings et al 2007), and persists in the inner cell mass (Spikings et al 2007) and up to gastrulation, most likely filters the levels of variants persisting in the offspring. This process is aided by the shedding of mtDNA during preimplantation development (Stigliani et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This may represent a nuclear response to decreased content of mitochondrial DNA (mtDNA) (Lloyd et al, 2006), which was found reduced in undifferentiated human ES and iPS cells (Armstrong et al 2010;Prigione et al, 2010). Indeed, cells depleted of mtDNA have been shown to induce the expression of mitochondrial biogenesis factors (Holmuhamedov et al, 2003) and POLG expression was upregulated in cells harboring large deletions of mtDNA (Alemi et al, 2007).…”
Section: Applying the "Metabolic State Hypothesis" To Reprogramming mentioning
confidence: 99%
“…However, the same genes have been found up-regulated upon differentiation of human mesenchymal stem cells (Chen et al, 2008) and mouse ES cells (Facucho-Oliveira et al, 2007). The most likely explanation of these conflicting results may be that the nuclear response is depending on the mtDNA content (Mercy et al, 2005;Lloyd et al, 2006) which may vary within different cell types or different time points. Interestingly, within teratoma samples, some genes involved in both mitochondrial biogenesis and bioenergetic metabolism were up-regulated compared to undifferentiated cells, suggesting a different mitochondrial response during in vitro and in vivo spontaneous differentiation of human pluripotent cells, possibly due to the tumorigenic nature of teratomas.…”
Section: Applying the "Metabolic State Hypothesis" To Reprogramming mentioning
confidence: 99%